Resilience and Recovery at Royal Courts, 1200-1840 - Persson, Fabian; Price, Munro; Recca, Cinzia (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book demonstrates the evolution of resilience and recovery as a concept by applying it to a new context, that of courts and monarchies. These were remarkably resilient institutions, with a strength and malleability that allowed them to 'bounce back' time and again. This volume highlights the different forms of resilience displayed in European courts during the medieval and early modern periods. Drawing on rarely published sources, it demonstrates different models of monarchical resilience, ranging from the survival of sovereign authority in political crisis, to the royal response to pandemic challenges, to other strategies for resisting internal or external threats. Resilience and Recovery illustrates how symbolic legitimacy and effective power were strongly intertwined, creating a distinct collective memory that shaped the defence of monarchical authority over many centuries. Fabian Persson is a Lecturer and Associate Professor in History at Linnaeus University in Sweden and specialises in the Swedish court with a particular interest in women and power. Munro Price is Professor of Modern European History at the University of Bradford, UK, and specializes in late eighteenth and early nineteenth-century French political and diplomatic history. Cinzia Recca is senior lecturer in Early Modern History at the University of Catania, Italy, in the Department of Education. Her main field of research includes the European Enlightenment, especially with regard to court studies and women's roles.
1 Resilience: An Introduction -- 2 Two Sisters, Two Towns, Two Kings: Facing War and Still Ruling -- 3 Hungaria Hispanica: Resilient Hungary and Its Integration into the Spanish Habsburg System, 1558-1648 -- 4 The Futility of Madame: Marguerite of Lorraine and Elisabeth-Charlotte of the Palatinate in the Service of Their Threatened Homelands -- 5 Francis Taaffe, Third Earl of Carlingford, and the House of Lorraine's Exile and Restoration, 1670-1704 -- 6 Ex vulnere vigor: Emblematic Representations of Resilience in the Royal Festivals in Honour of Pedro II (1648-1707), King of Portugal -- 7 The Eighteenth-Century Crisis in the European Order and Victor Amadeus II as a Model of Resilience for Italian Patriotism and Cultural Unity -- 8 Charles of Bourbon, King of Southern Italy (1734-1759): The Resilience of the Neapolitan 'Nation', the Development of Reformism and the Strength of the Reaction -- 9 The European Catholic Dynasties and the Fight Against Smallpox: Bourbon Rulers Between Resilient and Resistant Actions -- 10 Resilience Born of Desperation: Keeping Dynasties Going in Eighteenth-Century Europe -- 11 Resilience and Revolution: The Defence of the Dynastic Interests of Charles IV and Maria Luisa of Parma in the Changing World of the Late Eighteenth Century -- 12 The Resilience and Resistance of the Bourbon Monarchy in the Kingdom of Naples (1799-1802) -- 13 'We Alone Know': How King Frederick VI of Denmark and His Regime Coped with Defeat in 1814 -- 14 'Cholera Adunque è Malattia Nervosa': The 1836-1837 Cholera Epidemic in the Kingdom of the Two Sicilies: Reception, Resilience, and Revolution.
Keywords: Europe -- History; Civilization -- History; World politics; Europe -- History -- 476-1492.; Europe -- History -- 1492-.; European History; Cultural History; Political History; History of Medieval Europe; History of Early Modern Europe; History of Modern Europe